CHARACTER EDUCATION IN PRODUCING ISLAMIC PERSONALITY - Samir, Maskur (Universitas Islam Negeri Banda Aceh, 2013)
Character education is necessary to be seriously concern in facing modernization. It is believed that character is one of elements to reach the aims of education. Precisely, education is an effort to form inner strength, behavior, as well mind. This article focuses on method and strategy to build the character which subsequently build personality refers to the Islamic fundamental sources namely as being commanded by Allah through His Prophet. There are some ways being introduced in the article to form good personality through building character optimally. First is to infuse positive thinking upon Allah as the Creator of good and bad personality. Second, good personality could only be reached by strongly cling to values as it was conducted by the Prophet. Third is inculcating simple act though it may seem elementary but key factor in forming one's character which subsequently form one's personality.